Diseminasi dan Akselerasi Percepatan Produksi Jamur Tiram Melalui Studi Kasus Mesin Press Baglog Otomatis di UD Zaida Jamur Tiram - Iriaji; Purnomo; Agusta Rakhmat Taufani; Mohamad Firzon Ainur Roziqin; Eka Putri Surya; Adinda Marcelliantika; Surasak Jamnongsarn; Alby Aruna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The program for implementing this activity aims to accelerate the production of oyster mushrooms at UD Zaida Oyster Mushrooms through dissemination and implementation of an automatic baglog press machine. This activity was carried out in collaboration between a team from the university and UD Zaida, integrating modern technology into traditional production processes. Through a series of training and workshops, implementation partners can operate machines effectively and understand optimal production management. The results of this activity show a significant increase in production capacity, where UD Zaida was able to increase oyster mushroom production output and reduce production waste. This program has also succeeded in increasing the skills and knowledge of workers, while providing a positive impact on the local economy through increasing income and employment opportunities. The dissemination of automatic baglog press machines has proven to be a sustainable solution that drives efficiency and productivity in the mushroom farming sector. This implementation activity recommends expanding the use of this technology to other regions as an effort to support the growth of the oyster mushroom industry at the national level.